(untitled) (Baltimore, 1992)
Many recent changes in the practice of Cardiology neccessitated extensive revisions in this third edition. The application of new diagnostic tests, therapeutic procedures, and drugs are introduced throughout the text.
Keywords: Heart,Cardiology,Tim mạch,Tim; Diseases